2011
DOI: 10.1177/1065912911421015
|View full text |Cite
|
Sign up to set email alerts
|

God Save This Honorable Court

Abstract: If Supreme Court behavior is structured largely by the policy preferences of the justices, political scientists ought to consider the source of those preferences. Religion is one force that can strongly shape a judge’s worldview and therefore her or his votes. In this article, the author examines the effect of religion on U.S. Supreme Court votes in eleven issue areas plausibly connected to religious values. Catholic justices vote in ways that more closely adhere to the teachings of the Catholic Church than do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…One 2004 study of district and appeals court judges, for example, found that "the religious background of judges proved to be the single most prominent feature"; 38 similarly, a 2012 analysis of Roman Catholic justices' voting record concluded that "religion is a source of judicial policy preferences, independent of underlying differences in ideology and justice-specific fixed effects." 39 By contrast, a 2013 study reached more modest conclusions concerning the differences between Roman Catholic and mainline Protestant justices, 40 and a 2015 article called into question the methodological presuppositions informing earlier studies' accounts of Roman Catholics on the Court. 41 As this sample of scholarship already attests, questions concerning justices' religious allegiances have been particularly pressing for the Court's Roman Catholic constituency.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…One 2004 study of district and appeals court judges, for example, found that "the religious background of judges proved to be the single most prominent feature"; 38 similarly, a 2012 analysis of Roman Catholic justices' voting record concluded that "religion is a source of judicial policy preferences, independent of underlying differences in ideology and justice-specific fixed effects." 39 By contrast, a 2013 study reached more modest conclusions concerning the differences between Roman Catholic and mainline Protestant justices, 40 and a 2015 article called into question the methodological presuppositions informing earlier studies' accounts of Roman Catholics on the Court. 41 As this sample of scholarship already attests, questions concerning justices' religious allegiances have been particularly pressing for the Court's Roman Catholic constituency.…”
mentioning
confidence: 98%
“…42 Both the scholarly community and the public media have raised questions about Roman Catholic Justices' potential responsiveness to their tradition's priorities; while results vary, the specter of undue influence remains. 43 And yet, Roman Catholic justices have shown no greater propensity towards citing Catholic amicus briefs than have their non-Catholic colleagues; indeed, some of the harshest critique of this practice and the alleged democratic impulse that propels it has come from one of the most stalwart Catholic justices of the past decades. 44 This survey merely skims the surface of scholarship on amicus curiae participation in the United States.…”
mentioning
confidence: 99%